A Longitudinal Study of Acculturation in Context and Cardiovascular Health and Their Effects on Cognition Among Older Latino Adults - Melissa Lamar; Mayra L. Estrella; Ana W. Capuano; Sue Leurgans; Debra A. Fleischman; Lisa L. Barnes; Brittney S. Lange‐Maia; David A. Bennett; David X. Marquez (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background We previously outlined the importance of considering acculturation within the context of older Latino adults' lived experience (ie, acculturation in context) to better capture contributors to cognitive aging. We now examine this conceptual framework as related to level of and change in cardiovascular health, and whether cardiovascular health modifies previously documented associations of acculturation in context with cognition. Methods and Results Acculturation in context data from 192 Latino participants without dementia at baseline (age ~70 years) were compiled into 3 separate composite scores: acculturation‐related (nativity, language‐, and social‐based preferences), contextually related socioenvironmental (experiences of discrimination, social isolation, social networks), and familism‐related (Latino‐centric family ethos). A modified American Heart Association's Life's Simple 7 (mLS7; ie, smoking, physical activity, body mass index, blood pressure, total cholesterol, blood glucose) was used to measure cardiovascular health. Mixed effects regressions simultaneously tested the association of all 3 composite scores with total mLS7 adjusting for confounders. Separate models tested whether mLS7 modified associations of the 3 composite scores and cognition. The contextually related socioenvironmental composite score reflecting higher discrimination, higher social isolation, and smaller social networks (estimate=0.22, SE=0.10, P=0.02) and the familism score (estimate=0.16, SE=0.07, P=0.02) both significantly associated with change in total mLS7. The acculturation‐related composite was not significantly associated with change in mLS7. No composite was significantly associated with level of mLS7. Total mLS7, however, significantly modified associations between the acculturation‐related composite and change in working memory (estimate=−0.02, SE=0.01, P=0.043). Conclusions Acculturation within the context of older Latino adults' lived experience is important for maintaining cardiovascular health, relationships that also affect domain‐specific cognitive decline.